GAMBARAN BEBAN KERJA PERAWAT PADA MASA PANDEMI COVID-19 DI RUMAH SAKIT UMUM DAERAH PANDAN ARANG BOYOLALI: GAMBARAN BEBAN KERJA PERAWAT PADA MASA PANDEMI COVID-19 DI RUMAH SAKIT UMUM DAERAH PANDAN ARANG BOYOLALI - Erliana Dilantari; Dewi Kartika Sari (Universitas Duta Bangsa Surakarta, 2023)
Introduction: during the COVID-19 pandemic nurses will sacrifice themselves to actively participate in their work against the COVID-19 pandemic. Due to the increasing number of confirmed cases and the number of deaths due to COVID-19, nurses are urgently needed in a hospital as someone who is professional in an effort to provide nursing care to patients with varied work demands. The emergency measures taken by the Hospital to continue to safely treat COVID-19 and non-COVID-19 patients have an impact on changes in the work, initial schedule and work patterns of nurses, which can lead to an increase in the workload of nurses Objectives: knowing the description of the workload of nurses during the COVID-19 pandemic at the Pandan Arang Regional General Hospital, Boyolali Methods: this research is a descriptive research with a cross sectional approach. Sampling using purposive sampling method with a sample of 60 respondents. The research instrument is a questionnaire. Data analysis used univariate statistical test Results: during the COVID-19 pandemic, the majority of nurses had a heavy workload (58.3%) and some nurses had a moderate workload during the pandemic (41.7%) Conclusions: during the COVID-19 pandemic nurses had a hard work